Method for manufacturing second-type low-smoke halogen-free standard wall cable of motor train unit
通过在动车组电缆中采用合金化铜单丝导体、低烟无卤材料绝缘层和护套、蜂窝状缓冲隔离层和双层屏蔽结构,解决了传统电缆在复杂工况下的导电性能不稳定、机械性能不足和电磁干扰难以抵御的问题,实现了更高的电缆性能和动车组安全性。
Patent Information
- Application Number
- CN202411860294.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional EMU cables have unstable electrical conductivity under complex operating conditions, insufficient mechanical properties, and difficult to resist electromagnetic interference. In addition, halogen-containing materials produce toxic gases during fire, affecting safety and environmental protection.
The alloyed copper monofilament conductor is used to improve the conductivity stability and mechanical strength through layered twisting and nanoceramic coating; the insulation layer and sheath are made of low-smoke and halogen-free materials, combined with a honeycomb buffer isolation layer and a double-layer shielding structure to enhance the insulation, bending and electromagnetic interference resistance of the cable.
It significantly improves the conductivity stability, mechanical properties and electromagnetic interference resistance of the cable, reduces the smoke density and halogen acid gas release during fire, and improves the electrical system reliability and fire safety of the EMU.
Smart Images

Figure CN119673566A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, and in particular to a method for manufacturing a second type low-smoke halogen-free standard wall cable for electric multiple units. Background Art
[0002] With the rapid development of rail transit technology, EMUs, as efficient and fast means of transportation, have increasingly stringent requirements for the performance and safety of their internal electrical systems. Cables, as the key carrier of power and signal transmission in the electrical system of EMUs, are also facing unprecedented challenges and higher standards under this development trend.
[0003] Traditional EMU cables have gradually exposed many limitations in long-term practical applications. In terms of electrical performance, the conductors of ordinary cables are mostly made of pure copper or conventional alloy materials, and their electrical conductivity is easily affected under complex working conditions. Under the vibration and electromagnetic environment interference caused by the frequent acceleration, deceleration and high-speed operation of the EMU, the resistance stability of the conductor is insufficient, which easily leads to increased power transmission loss, and signal transmission may also be distorted or interrupted. Moreover, the shielding measures of traditional cables are relatively simple, and it is difficult to effectively resist the increasingly complex electromagnetic interference sources in modern EMUs, such as broadband electromagnetic radiation generated by various electronic equipment and power systems, thus affecting the overall reliability of the electrical system and the signal transmission quality. In terms of mechanical properties, conventional cables have limited bending and tensile resistance. The wiring space inside the EMU is small and the direction is complex, and the cable needs to be bent frequently and withstand a certain amount of axial tension. Traditional cables are prone to structural deformation in this environment, such as conductor breakage, insulation layer rupture, etc., which can cause short-circuit failures in severe cases, threatening the operation safety of the EMU. In addition, the bonding between the various layers of the traditional cable structure is not tight and stable enough. During long-term use, it is easy to cause separation between the layers or the formation of bubbles due to factors such as vibration and temperature changes, further weakening the mechanical properties of the cable. In terms of fire prevention and environmental protection performance, although traditional halogen-containing cables have certain flame retardancy, they will release a large amount of toxic and harmful gases and thick smoke when burned. In a crowded and closed space environment such as an EMU, once a fire occurs, the thick smoke and halogen acid gas produced by the halogen-containing cables will not only seriously hinder the escape of passengers and the development of rescue work, but also cause great harm to the lives and health of personnel. Moreover, halogen-containing cables will also cause long-term pollution to the environment during the production and disposal process, which does not meet the strict requirements of modern society for environmental protection.
[0004] In summary, with the continuous advancement of EMU technology, there is an urgent need for a new type of cable that has significant improvements in electrical performance, mechanical performance, fire protection and environmental protection performance, can adapt to complex working conditions and has high reliability. Summary of the invention
[0005] The purpose of the present invention is to provide a method for manufacturing the second type of low-smoke halogen-free standard wall cable for EMUs, which ensures conductive stability and protection through layered twisting of alloyed copper monofilament conductors and nano-ceramic coatings, realizes flame retardant insulation through the insulating layer composite system, buffers external forces through the buffer isolation layer, and has a double-layer structure for the shielding layer to resist electromagnetic interference. The reinforced core enhances axial tension, and the sheath composite system and microcapsules provide protection and functions. Through multi-step collaborative construction and post-processing detection, high performance in electrical, mechanical, fire protection, environmental protection and other aspects is achieved to adapt to the complex working conditions of the EMU and ensure operational reliability.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for manufacturing a second type low-smoke zero-halogen standard wall cable for a train set, characterized by comprising the following steps: S1: Conductor preparation, S2: Insulation extrusion, S3: Buffer isolation layer molding, S4: Shielding layer production, S5: Preparation and installation of reinforcement core, S6: Sheath extrusion step, S7: post-processing step; Step S1: The conductor is prepared by twisting a plurality of metal monofilaments, wherein the metal monofilaments are alloyed copper monofilaments, and the alloying elements include cerium and titanium, and the total content of the cerium and titanium in the copper monofilaments is 0.05%-0.15%; When the monofilaments are twisted, a layered twisting method is adopted, which is divided into three layers: inner, middle and outer. The inner layer twisting pitch is 8-12 mm, the middle layer twisting pitch is 12-16 mm, and the outer layer twisting pitch is 16-20 mm. The conductor surface is treated with a nano-ceramic coating with a coating thickness of 50-100 nanometers. The nano-ceramic coating material is a composite ceramic of aluminum oxide and titanium dioxide, wherein the mass ratio of aluminum oxide to titanium dioxide is 3:1-5:1. The deposition of the nano-ceramic coating adopts a chemical vapor deposition method, the reaction gas is a mixed vapor of trimethyl aluminum, titanium tetrachloride and cerium nitrate hexahydrate, the deposition temperature is 400-500°C, the reaction pressure is 100-200 Pa, and the deposition time is 30-60 minutes.
[0007] In step S2, insulation is extruded and coated on the outside of the conductor. The insulation layer is made of low-smoke halogen-free material. The low-smoke halogen-free material is a composite system of ethylene-vinyl acetate copolymer, silicone elastomer and new phosphorus-nitrogen flame retardant. The mass ratio is 6:3:1-5:4:1. The thickness of the insulation layer is between 0.8-1.2 mm.
[0008] Step S3: a buffer isolation layer is formed outside the insulating layer and is made of a thermoplastic polyurethane material. The interior of the layer is a honeycomb structure, and the honeycomb pores are filled with glass beads with a diameter of 0.1-0.3 mm. The thermoplastic polyurethane material and the glass beads are mixed in an internal mixer at a mixing temperature of 120-150°C for 5-10 minutes. The buffer isolation layer has a thickness of 0.3-0.5 mm and is formed by a co-extrusion process. The extrusion is carried out continuously with the insulating layer on the same production line, and the co-extrusion mold temperature is 190-210°C.
[0009] Step S4: The shielding layer is made and arranged outside the buffer isolation layer. The shielding layer has a double-layer structure. The inner layer is a silver-plated copper foil wrapping layer. The wrapping overlap rate is between 25% and 35%. The copper foil thickness is between 0.05 and 0.1 mm. The silver plating thickness is between 3 and 5 microns. Constant tension wrapping equipment is used during wrapping, and the tension is controlled at 5-10N. The outer layer uses high magnetic permeability amorphous alloy wire for woven shielding. The weaving density is not less than 85%, and the diameter of the amorphous alloy wire is between 0.1 and 0.2 mm. The weaving adopts a 16-24 spindle weaving machine with a weaving angle of 45-60 degrees.
[0010] Step S5: Preparation and installation of the reinforcing core: The reinforcing core is passed through the shielding layer along the axial direction of the cable. The reinforcing core is formed by twisting multiple aramid fiber bundles. The aramid fiber bundles are wrapped with a layer of polyimide film. The aramid fiber bundles are first pre-stretched under a tension of 3-5N, and then twisted with a pitch of 10-15 mm. After twisting, they are heat treated at 200-250°C for 10-15 minutes. The diameter of the reinforcing core is 1-2 mm.
[0011] Step S6: a sheath extrusion step is applied to the shielding layer. The sheath is made of a composite system of low-smoke halogen-free polyolefin material and long fiber reinforced material. The long fiber reinforced material is basalt fiber, which has a length of 3-5 mm and a volume fraction of 10%-15% in the sheath. The low-smoke halogen-free polyolefin material and the basalt fiber are mixed in a twin-screw extruder, the screw speed is 40-60 rpm, and the mixing temperature is 180-200°C. The thickness of the sheath is between 1.5-2.5 mm, and the outer surface of the sheath is provided with an anti-slip texture. Lubricants and ultraviolet absorbers are encapsulated in the microcapsules. The microcapsules are prepared by in-situ polymerization, with urea-formaldehyde resin as the wall material, and lubricants and ultraviolet absorbers as the core materials. The reaction temperature during the preparation process is 60-70°C, the reaction time is 2-3 hours, the amount of microcapsules added to the sheath material is 5%-10%, and when the sheath is extruded, a vacuum extruder is used, the extrusion temperature is 200-220°C, and the vacuum degree is 0.05-0.1 MPa.
[0012] The post-processing step of step S7 is specifically to cool and reel the cable, and conduct a comprehensive test including electrical performance, mechanical performance and combustion performance testing.
[0013] The bending radius of the cable is not greater than 10 times the outer diameter of the cable, and after 1000 repeated bending tests, the attenuation rates of the electrical and mechanical properties of the cable are both less than 5%.
[0014] During the preparation and installation of the reinforcing core in step S5, during the twisting process of the aramid fiber bundles, a fiber positioning spacer is added every 5-10 mm to ensure the uniformity and stability of the twisted structure.
[0015] First, in the conductor preparation stage, alloyed copper monofilaments containing trace amounts of cerium and titanium and with a total content precisely controlled at 0.05%-0.15% are selected as the basic material. The presence of cerium can effectively refine the copper grains and greatly improve the strength and toughness of the copper monofilaments, while titanium gives it excellent corrosion resistance and high-temperature stability, thereby ensuring that the conductor always maintains good conductivity under complex and changing working conditions. These monofilaments are uniquely layered and twisted, divided into three layers: inner, middle and outer, with twisting pitches of 8-12 mm, 12-16 mm and 16-20 mm respectively. When the cable encounters external forces such as bending or stretching, this layered twisted structure can cleverly distribute stress between the layers. Subsequently, a nano-ceramic coating with a thickness of 50-100 nanometers is deposited on the surface of the conductor using chemical vapor deposition, and its material is a composite ceramic of aluminum oxide and titanium dioxide with a mass ratio of 3:1-5:1. The high hardness and wear resistance of alumina provide physical protection for the conductor surface, resisting external mechanical damage such as friction and scratches. The good chemical stability of titanium dioxide effectively prevents the conductor from corroding in humid, acidic, and alkaline chemical environments.
[0016] In the insulation extrusion step, a low-smoke, halogen-free composite system composed of ethylene-vinyl acetate copolymer, silicone elastomer and new phosphorus-nitrogen flame retardant in a mass ratio of 6:3:1-5:4:1 is used as the insulation material. Ethylene-vinyl acetate copolymer gives the insulation layer good flexibility and processing properties, so that it can adapt to the installation and use requirements of cables in different environments, and effectively prevent the insulation layer from cracking or damage due to mechanical stress. The silicone elastomer brings excellent elasticity and tear resistance to the insulation layer. Even if the cable is subjected to large external forces such as bending, stretching or extrusion, the insulation layer can still remain intact, reliably preventing short-circuit failures between conductors. The addition of new phosphorus-nitrogen flame retardants is the key to meeting the fire safety requirements of cables. When burning, it can quickly decompose and produce a large amount of non-combustible gases, such as nitrogen and ammonia, which can dilute the oxygen concentration in the surrounding air and inhibit the spread of flames. At the same time, a dense carbonized layer is formed on the burning surface to isolate oxygen from the contact with combustible substances, thereby effectively preventing the fire from spreading, effectively ensuring the safety of cables in the event of fire, and reducing the threat of fire to the safety of EMU operation. The thickness of the insulation layer is set between 0.8-1.2 mm to ensure sufficient insulation performance, while avoiding the increase in the overall volume and weight of the cable due to the excessive thickness of the insulation layer, which affects the convenience of cable installation and laying.
[0017] When the buffer isolation layer is formed, thermoplastic polyurethane material is used to construct an internal honeycomb structure, and the honeycomb holes are filled with glass beads with a diameter of 0.1-0.3 mm. Thermoplastic polyurethane material itself has high elasticity and tear resistance, which can provide additional buffering protection for the internal structure of the cable. When the cable is hit or squeezed, the impact force first acts on the buffer isolation layer, and the honeycomb structure undergoes elastic deformation, which evenly disperses the impact force into each honeycomb unit, and the glass beads filled therein further enhance the buffering effect. Thermoplastic polyurethane material and glass beads are mixed in an internal mixer at 120-150°C for 5-10 minutes to ensure that the two are fully mixed and evenly distributed, so that the glass beads are stably distributed in the thermoplastic polyurethane material to form a composite structure. The buffer isolation layer has a thickness of 0.3-0.5 mm and is continuously formed on the same production line as the insulation layer using a co-extrusion process. The co-extrusion mold temperature is controlled at 190-210°C. This co-extrusion process ensures a close bond between the buffer isolation layer and the insulation layer, effectively avoiding defects such as interlayer separation or bubbles, and improving the stability and reliability of the overall cable structure.
[0018] The shielding layer production process adopts a double-layer structure. The inner layer is a silver-plated copper foil wrapping layer, the wrapping overlap rate is between 25%-35%, the copper foil thickness is between 0.05-0.1 mm, and the silver plating thickness is between 3-5 microns. When wrapping, the tension is controlled at 5-10N with the help of a constant tension wrapping device. The silver-plated copper foil wrapping layer mainly undertakes the electromagnetic shielding function. The silver plating layer effectively reflects and absorbs external electromagnetic interference signals with good conductivity, preventing these interference signals from affecting the electrical signals transmitted inside the cable, and ensuring the accuracy and stability of signal transmission. The copper foil provides a supporting structure for the silver plating layer, and it also has a certain electromagnetic shielding capability. Accurately control the wrapping overlap rate, copper foil thickness, silver plating thickness and wrapping tension to ensure the uniformity and reliability of the shielding effect of the silver-plated copper foil wrapping layer. The outer layer uses high-permeability amorphous alloy wire for braided shielding, with a braiding density of no less than 85%. The diameter of the amorphous alloy wire is between 0.1-0.2 mm, and it is braided using a 16-24 spindle braiding machine at a braiding angle of 45-60 degrees. The high-permeability amorphous alloy wire can play an excellent shielding role against low-frequency magnetic field interference, and work together with the inner silver-plated copper foil wrapping layer to build a full range of electromagnetic shielding system, effectively resisting electromagnetic interference in different frequency ranges. Whether it is electromagnetic noise from the external environment or electromagnetic radiation generated by other electrical equipment inside the EMU, it can be shielded to the maximum extent, ensuring the quality of various electrical signals such as control signals and communication signals transmitted by the cable, and improving the overall reliability and stability of the EMU electrical system.
[0019] During the preparation and installation of the reinforcing core, multiple aramid fiber bundles are twisted together and penetrate the shielding layer along the axial direction of the cable. A layer of polyimide film is wrapped around the aramid fiber bundle. Aramid fiber has extremely high strength and modulus and is an ideal reinforcing material. During preparation, the aramid fiber bundle is first pre-stretched under a tension of 3-5N. This step can make the fibers inside the aramid fiber bundle more neatly and tightly arranged, remove internal stress, improve fiber orientation, and give full play to the high strength performance of aramid fiber. Then it is twisted at a pitch of 10-15 mm, and after twisting, it is heat treated at 200-250℃ for 10-15 minutes. The heat treatment can further enhance the bonding force between the aramid fiber bundles and make the twisted structure more stable. The diameter of the reinforcing core after twisting is 1-2 mm, which can provide strong axial tensile strength for the cable, effectively preventing the cable from being stretched, deformed or broken due to axial tension during laying, installation or operation. The polyimide film wrapped around the aramid fiber bundle has excellent insulation, high temperature resistance and mechanical properties. It can protect the aramid fiber bundle from external environmental erosion, such as moisture, chemicals, etc., and prevent the aramid fiber bundle from electrochemical reactions or friction damage with other components inside the cable, further improving the durability and reliability of the reinforcing core. During the twisting process of the aramid fiber bundle, a fiber positioning separator is added every 5-10 mm to ensure the uniformity and stability of the twisted structure. The fiber positioning separator can prevent the aramid fiber bundle from deflecting, entangled or locally stacked during the twisting process, ensure the uniform cross-sectional area of the reinforcing core, and make the reinforcing core evenly stressed when subjected to axial tension, avoiding premature failure of the reinforcing core due to local stress concentration, thereby improving the overall performance and service life of the reinforcing core.
[0020] In the sheath extrusion step, a composite system of low-smoke halogen-free polyolefin material and long fiber reinforcement material is used. The long fiber reinforcement material is basalt fiber with a length of 3-5 mm and a volume fraction of 10%-15% in the sheath. Low-smoke halogen-free polyolefin material provides basic flexibility, weather resistance and certain mechanical strength, which can protect the internal structure of the cable from physical damage from the external environment, such as ultraviolet radiation, wind and rain, mechanical collision, etc. As a long fiber reinforcement material, basalt fiber has excellent properties such as high strength, high modulus, high temperature resistance and corrosion resistance. Its addition significantly improves the overall strength and rigidity of the sheath. The two are mixed in a twin-screw extruder, the screw speed is controlled at 40-60 rpm, and the mixing temperature is 180-200℃. In this mixing process, the reasonable control of the screw speed and mixing temperature of the twin-screw extruder is the key to ensure uniform mixing of the two materials. The thickness of the sheath is between 1.5-2.5 mm, which can not only ensure the effective protection of the sheath to the internal structure of the cable, but also take into account the overall weight and cost of the cable. The outer surface of the sheath is treated with anti-skid texture. Lubricants and ultraviolet absorbers are encapsulated in the microcapsules. The microcapsules are prepared by in-situ polymerization, with urea-formaldehyde resin as the wall material, lubricants and ultraviolet absorbers as the core material. The reaction temperature during the preparation process is 60-70°C, the reaction time is 2-3 hours, and the amount of microcapsules added to the sheath material is 5%-10%. When the sheath is extruded, a vacuum extruder is used, the extrusion temperature is 200-220°C, and the vacuum degree is 0.05-0.1 MPa. The anti-skid texture can increase the surface friction of the sheath, facilitate the cable laying and installation operations, and prevent the cable from being damaged due to sliding during the installation process. The lubricant in the microcapsule can be slowly released during the use of the cable, reducing the friction coefficient between the sheath and external objects, reducing the wear of the cable in dynamic processes such as bending and stretching, and extending the service life of the cable. The ultraviolet absorber can absorb ultraviolet radiation, prevent the sheath from aging and degradation due to long-term exposure to sunlight, and maintain the physical properties and appearance integrity of the sheath.
[0021] Finally, in the S7 post-processing step, the cable is cooled, reeled, and fully tested, including electrical performance, mechanical performance, and combustion performance testing. The cooling process allows the cable to quickly cool down and solidify after extrusion, stabilizing the cable structure and size. The reeling process neatly winds the finished cable onto a reel for easy storage, transportation, and subsequent installation and use.
[0022] Compared with the prior art, the present invention has the following beneficial effects: The alloyed copper monofilament containing cerium and titanium is used. The cerium refines the grains and the titanium enhances the corrosion resistance and stability, making the conductor more conductive and stable under complex working conditions. The layered twisted structure effectively distributes stress and reduces the risk of resistance change caused by external forces. Compared with traditional single-material and simple twisted conductors, it can better maintain a stable low-resistance state and reduce power transmission losses.
[0023] Nano-ceramic coating not only improves insulation, but its uniform and dense characteristics can also reduce local discharge, ensure the integrity and accuracy of electrical signal transmission, perform better in high-frequency signal transmission scenarios, and reduce signal distortion.
[0024] The double-layer structure of silver-plated copper foil wrapping and high-permeability amorphous alloy wire braided shielding forms a broadband electromagnetic shielding system. Compared with traditional single-layer shielded cables, it can more effectively resist external electromagnetic interference, whether it is electromagnetic noise from surrounding electrical equipment or complex electromagnetic radiation generated by the EMU's own power system, it can be efficiently shielded, ensuring the purity and stability of various electrical signals such as control signals and communication signals transmitted by the cable, greatly improving the anti-interference ability and signal transmission quality of the EMU electrical system.
[0025] The layered twisted structure of the conductor allows for reasonable stress dispersion during bending and stretching. The honeycomb structure of the buffer isolation layer combined with glass beads effectively absorbs and disperses external force impacts. The aramid fiber bundles of the reinforcing core provide strong axial tensile strength. These designs work together. Compared with traditional cables, this cable has significantly improved bending and tensile resistance, and can withstand greater mechanical stress without structural damage or performance degradation.
[0026] The co-extrusion process of the buffer isolation layer and the insulation layer ensures a tight bond between the layers without separation or bubble defects. The fiber positioning separators in the preparation of the reinforcing core ensure a uniform and stable twisted structure to avoid local stress concentration. During long-term use, the synergy between the layers is always good, effectively preventing performance degradation caused by structural deformation or interlayer slippage, extending the service life of the cable, and reducing maintenance costs and replacement frequency.
[0027] The new phosphorus-nitrogen flame retardant in the insulation layer can quickly decompose to produce a large amount of non-combustible gas and form a carbonized layer when burning, effectively preventing the spread of fire. Compared with traditional halogen-containing flame-retardant cables, the smoke density level and halogen acid gas release during combustion are greatly reduced. When a fire occurs, low smoke density can ensure visibility inside the car, facilitate passenger escape and rescue operations, and low halogen acid gas release reduces the toxic effects of toxic and harmful gases on personnel, providing a strong guarantee for the fire safety of EMUs and meeting the strict requirements of modern rail transit for fire safety.
[0028] The low-smoke halogen-free material system is adopted, and no harmful halogen elements are contained in the insulation layer or the sheath. The harm to the environment and human health is minimal during production, use and disposal. Compared with traditional halogen-containing cables, the pollution risk to the atmosphere, soil and water bodies is reduced, which conforms to the environmental protection concept of sustainable development, is conducive to the EMU to achieve higher standards in environmental protection, and enhances the environmental protection image and social responsibility of the enterprise.
[0029] The nano-ceramic coating of the conductor, the reasonable selection of the insulation material and the addition of UV absorbers in the sheath make the cable have excellent weather resistance. Whether in harsh environmental conditions such as high temperature, humidity, acid and alkali, or in long-term UV irradiation environment, the cable's various properties can remain relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of a method for manufacturing a second type low-smoke halogen-free standard wall cable for a train set. Specific implementation methods
[0031] The technical solutions in the embodiments of the present invention will be fully described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0032] like Figure 1 As shown, A method for manufacturing a second type low-smoke zero-halogen standard wall cable for a train set, characterized by comprising the following steps: S1: Conductor preparation, S2: Insulation extrusion, S3: Buffer isolation layer molding, S4: Shielding layer production, S5: Preparation and installation of reinforcement core, S6: Sheath extrusion step, S7: post-processing step; Step S1: The conductor is prepared by twisting a plurality of metal monofilaments, wherein the metal monofilaments are alloyed copper monofilaments, and the alloying elements include cerium and titanium, and the total content of the cerium and titanium in the copper monofilaments is 0.05%-0.15%; When the monofilaments are twisted, a layered twisting method is adopted, which is divided into three layers: inner, middle and outer. The inner layer twisting pitch is 8-12 mm, the middle layer twisting pitch is 12-16 mm, and the outer layer twisting pitch is 16-20 mm. The conductor surface is treated with a nano-ceramic coating with a coating thickness of 50-100 nanometers. The nano-ceramic coating material is a composite ceramic of aluminum oxide and titanium dioxide, wherein the mass ratio of aluminum oxide to titanium dioxide is 3:1-5:1. The deposition of the nano-ceramic coating adopts a chemical vapor deposition method, the reaction gas is a mixed vapor of trimethyl aluminum, titanium tetrachloride and cerium nitrate hexahydrate, the deposition temperature is 400-500°C, the reaction pressure is 100-200 Pa, and the deposition time is 30-60 minutes.
[0033] In step S2, insulation is extruded and coated on the outside of the conductor. The insulation layer is made of low-smoke halogen-free material. The low-smoke halogen-free material is a composite system of ethylene-vinyl acetate copolymer, silicone elastomer and new phosphorus-nitrogen flame retardant. The mass ratio is 6:3:1-5:4:1. The thickness of the insulation layer is between 0.8-1.2 mm.
[0034] Step S3: a buffer isolation layer is formed outside the insulating layer and is made of a thermoplastic polyurethane material. The interior of the layer is a honeycomb structure, and the honeycomb pores are filled with glass beads with a diameter of 0.1-0.3 mm. The thermoplastic polyurethane material and the glass beads are mixed in an internal mixer at a mixing temperature of 120-150°C for 5-10 minutes. The buffer isolation layer has a thickness of 0.3-0.5 mm and is formed by a co-extrusion process. The extrusion is carried out continuously with the insulating layer on the same production line, and the co-extrusion mold temperature is 190-210°C.
[0035] Step S4: The shielding layer is made and arranged outside the buffer isolation layer. The shielding layer has a double-layer structure. The inner layer is a silver-plated copper foil wrapping layer. The wrapping overlap rate is between 25% and 35%. The copper foil thickness is between 0.05 and 0.1 mm. The silver plating thickness is between 3 and 5 microns. Constant tension wrapping equipment is used during wrapping, and the tension is controlled at 5-10N. The outer layer uses high magnetic permeability amorphous alloy wire for woven shielding. The weaving density is not less than 85%, and the diameter of the amorphous alloy wire is between 0.1 and 0.2 mm. The weaving adopts a 16-24 spindle weaving machine with a weaving angle of 45-60 degrees.
[0036] Step S5: Preparation and installation of the reinforcing core: The reinforcing core is passed through the shielding layer along the axial direction of the cable. The reinforcing core is formed by twisting multiple aramid fiber bundles. The aramid fiber bundles are wrapped with a layer of polyimide film. The aramid fiber bundles are first pre-stretched under a tension of 3-5N, and then twisted with a pitch of 10-15 mm. After twisting, they are heat treated at 200-250°C for 10-15 minutes. The diameter of the reinforcing core is 1-2 mm.
[0037] Step S6: a sheath extrusion step is applied to the shielding layer. The sheath is made of a composite system of low-smoke halogen-free polyolefin material and long fiber reinforced material. The long fiber reinforced material is basalt fiber, which has a length of 3-5 mm and a volume fraction of 10%-15% in the sheath. The low-smoke halogen-free polyolefin material and the basalt fiber are mixed in a twin-screw extruder, the screw speed is 40-60 rpm, and the mixing temperature is 180-200°C. The thickness of the sheath is between 1.5-2.5 mm, and the outer surface of the sheath is provided with an anti-slip texture. Lubricants and ultraviolet absorbers are encapsulated in the microcapsules. The microcapsules are prepared by in-situ polymerization, with urea-formaldehyde resin as the wall material, and lubricants and ultraviolet absorbers as the core materials. The reaction temperature during the preparation process is 60-70°C, the reaction time is 2-3 hours, the amount of microcapsules added to the sheath material is 5%-10%, and when the sheath is extruded, a vacuum extruder is used, the extrusion temperature is 200-220°C, and the vacuum degree is 0.05-0.1 MPa.
[0038] The post-processing step of step S7 is specifically to cool and reel the cable, and conduct a comprehensive test including electrical performance, mechanical performance and combustion performance testing.
[0039] The bending radius of the cable is not greater than 10 times the outer diameter of the cable, and after 1000 repeated bending tests, the attenuation rates of the electrical and mechanical properties of the cable are both less than 5%.
[0040] During the preparation and installation of the reinforcing core in step S5, during the twisting process of the aramid fiber bundles, a fiber positioning spacer is added every 5-10 mm to ensure the uniformity and stability of the twisted structure.
[0041] The specific implementation method is: S1: Conductor preparation, the metal monofilament is an alloyed copper monofilament, the alloying elements include cerium and titanium, and the total content of cerium and titanium in the copper monofilament is 0.05%-0.15%; When the monofilaments are twisted, a layered twisting method is adopted, which is divided into three layers: inner, middle and outer. The inner layer twisting pitch is 8-12 mm, the middle layer twisting pitch is 12-16 mm, and the outer layer twisting pitch is 16-20 mm. The conductor surface is treated with a nano-ceramic coating with a coating thickness of 50-100 nanometers. The nano-ceramic coating material is a composite ceramic of aluminum oxide and titanium dioxide, wherein the mass ratio of aluminum oxide to titanium dioxide is 3:1-5:1. The deposition of the nano-ceramic coating adopts a chemical vapor deposition method, the reaction gas is a mixed vapor of trimethyl aluminum, titanium tetrachloride and cerium nitrate hexahydrate, the deposition temperature is 400-500°C, the reaction pressure is 100-200 Pa, and the deposition time is 30-60 minutes.
[0042] S2: Insulation extrusion, the insulation layer is made of low-smoke halogen-free material, the low-smoke halogen-free material is a composite system of ethylene-vinyl acetate copolymer, silicone elastomer and new phosphorus-nitrogen flame retardant, the mass ratio of which is 6:3:1-5:4:1, and the thickness of the insulation layer is between 0.8-1.2 mm.
[0043] S3: The buffer isolation layer is formed by thermoplastic polyurethane material, and its interior is a honeycomb structure. The honeycomb holes are filled with glass beads with a diameter of 0.1-0.3 mm. The thermoplastic polyurethane material and the glass beads are mixed in an internal mixer at a mixing temperature of 120-150°C for 5-10 minutes. The buffer isolation layer has a thickness of 0.3-0.5 mm and is formed by a co-extrusion process. It is continuously extruded with the insulation layer on the same production line. The co-extrusion mold temperature is 190-210°C.
[0044] S4: Shielding layer production, the shielding layer is a double-layer structure, the inner layer is a silver-plated copper foil wrapping layer, the wrapping overlap rate is between 25%-35%, the copper foil thickness is between 0.05-0.1 mm, the silver plating thickness is between 3-5 microns, and constant tension wrapping equipment is used during wrapping, and the tension is controlled at 5-10N. The outer layer uses high magnetic permeability amorphous alloy wire weaving shielding, and the weaving density is not less than 85%. The diameter of the amorphous alloy wire is between 0.1-0.2 mm, and the weaving adopts a 16-24 spindle weaving machine with a weaving angle of 45-60 degrees.
[0045] S5: Preparation and installation of the reinforcing core, which runs through the shielding layer along the axial direction of the cable. The reinforcing core is formed by twisting multiple aramid fiber bundles, and the aramid fiber bundles are wrapped with a layer of polyimide film. The aramid fiber bundles are first pre-stretched under a tension of 3-5N, and then twisted at a pitch of 10-15 mm. After twisting, they are heat treated at 200-250℃ for 10-15 minutes. The diameter of the reinforcing core is 1-2 mm. During the twisting process of the aramid fiber bundles, a fiber positioning separator is added every 5-10 mm to ensure the uniformity and stability of the twisted structure.
[0046] S6: a sheath extrusion step, wherein the sheath is made of a composite system of a low-smoke halogen-free polyolefin material and a long fiber reinforcement material, wherein the long fiber reinforcement material is a basalt fiber having a length of 3-5 mm and a volume fraction of 10%-15% in the sheath, and the low-smoke halogen-free polyolefin material and the basalt fiber are mixed in a twin-screw extruder, the screw speed is 40-60 rpm, and the mixing temperature is 180-200°C; The thickness of the sheath is between 1.5-2.5 mm, and the outer surface of the sheath is provided with an anti-slip texture. Lubricants and ultraviolet absorbers are encapsulated in the microcapsules. The microcapsules are prepared by in-situ polymerization, with urea-formaldehyde resin as the wall material, and lubricants and ultraviolet absorbers as the core materials. The reaction temperature during the preparation process is 60-70°C, the reaction time is 2-3 hours, the amount of microcapsules added to the sheath material is 5%-10%, and when the sheath is extruded, a vacuum extruder is used, the extrusion temperature is 200-220°C, and the vacuum degree is 0.05-0.1 MPa.
[0047] S7: Post-processing step; specifically, cooling and reeling the cable, and conducting comprehensive tests including electrical performance, mechanical performance and combustion performance tests.
[0048] The bending radius of the cable is not greater than 10 times the outer diameter of the cable, and after 1000 repeated bending tests, the attenuation rates of the electrical and mechanical properties of the cable are both less than 5%.
Claims
1. A method for manufacturing a second type low-smoke halogen-free standard wall cable for EMUs, characterized in that: The following steps are involved: S1: Conductor preparation, S2: Insulation extrusion, S3: Buffer isolation layer molding, S4: Shielding layer production, S5: Preparation and installation of reinforcement core, S6: Sheath extrusion step, S7: Post-processing step.
2. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: Step S1: The conductor is prepared by twisting a plurality of metal monofilaments, wherein the metal monofilaments are alloyed copper monofilaments, and the alloying elements include cerium and titanium, and the total content of the cerium and titanium in the copper monofilaments is 0.05%-0.15%; When the monofilaments are twisted, a layered twisting method is adopted, which is divided into three layers: inner, middle and outer. The inner layer twisting pitch is 8-12 mm, the middle layer twisting pitch is 12-16 mm, and the outer layer twisting pitch is 16-20 mm. The conductor surface is treated with a nano-ceramic coating with a coating thickness of 50-100 nanometers. The nano-ceramic coating material is a composite ceramic of aluminum oxide and titanium dioxide, wherein the mass ratio of aluminum oxide to titanium dioxide is 3:1-5:
1. The deposition of the nano-ceramic coating adopts a chemical vapor deposition method, the reaction gas is a mixed vapor of trimethyl aluminum, titanium tetrachloride and cerium nitrate hexahydrate, the deposition temperature is 400-500°C, the reaction pressure is 100-200 Pa, and the deposition time is 30-60 minutes.
3. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: In step S2, insulation is extruded and coated on the outside of the conductor. The insulation layer is made of low-smoke halogen-free material. The low-smoke halogen-free material is a composite system of ethylene-vinyl acetate copolymer, silicone elastomer and new phosphorus-nitrogen flame retardant. The mass ratio is 6:3:1-5:4:
1. The thickness of the insulation layer is between 0.8-1.2 mm.
4. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: Step S3: a buffer isolation layer is formed outside the insulating layer and is made of a thermoplastic polyurethane material. The interior of the layer is a honeycomb structure, and the honeycomb pores are filled with glass beads with a diameter of 0.1-0.3 mm. The thermoplastic polyurethane material and the glass beads are mixed in an internal mixer at a mixing temperature of 120-150°C for 5-10 minutes. The buffer isolation layer has a thickness of 0.3-0.5 mm and is formed by a co-extrusion process. The extrusion is carried out continuously with the insulating layer on the same production line, and the co-extrusion mold temperature is 190-210°C.
5. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: Step S4: The shielding layer is made and arranged outside the buffer isolation layer. The shielding layer has a double-layer structure. The inner layer is a silver-plated copper foil wrapping layer. The wrapping overlap rate is between 25% and 35%. The copper foil thickness is between 0.05 and 0.1 mm. The silver plating thickness is between 3 and 5 microns. Constant tension wrapping equipment is used during wrapping, and the tension is controlled at 5-10N. The outer layer uses high magnetic permeability amorphous alloy wire for woven shielding. The weaving density is not less than 85%, and the diameter of the amorphous alloy wire is between 0.1 and 0.2 mm. The weaving adopts a 16-24 spindle weaving machine with a weaving angle of 45-60 degrees.
6. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: Step S5: Preparation and installation of the reinforcing core: The reinforcing core is passed through the shielding layer along the axial direction of the cable. The reinforcing core is formed by twisting multiple aramid fiber bundles. The aramid fiber bundles are wrapped with a layer of polyimide film. The aramid fiber bundles are first pre-stretched under a tension of 3-5N, and then twisted with a pitch of 10-15 mm. After twisting, they are heat treated at 200-250°C for 10-15 minutes. The diameter of the reinforcing core is 1-2 mm.
7. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: Step S6: a sheath extrusion step is applied to the shielding layer. The sheath is made of a composite system of low-smoke halogen-free polyolefin material and long fiber reinforced material. The long fiber reinforced material is basalt fiber, which has a length of 3-5 mm and a volume fraction of 10%-15% in the sheath. The low-smoke halogen-free polyolefin material and the basalt fiber are mixed in a twin-screw extruder, the screw speed is 40-60 rpm, and the mixing temperature is 180-200°C. The thickness of the sheath is between 1.5-2.5 mm, and the outer surface of the sheath is provided with an anti-slip texture. Lubricants and ultraviolet absorbers are encapsulated in the microcapsules. The microcapsules are prepared by in-situ polymerization, with urea-formaldehyde resin as the wall material, and lubricants and ultraviolet absorbers as the core materials. The reaction temperature during the preparation process is 60-70°C, the reaction time is 2-3 hours, the amount of microcapsules added to the sheath material is 5%-10%, and when the sheath is extruded, a vacuum extruder is used, the extrusion temperature is 200-220°C, and the vacuum degree is 0.05-0.1 MPa.
8. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: The post-processing step of step S7 is specifically to cool and reel the cable, and conduct a comprehensive test including electrical performance, mechanical performance and combustion performance testing.
9. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: The bending radius of the cable is not greater than 10 times the outer diameter of the cable, and after 1000 repeated bending tests, the attenuation rates of the electrical and mechanical properties of the cable are both less than 5%.
10. The method for manufacturing the second type low-smoke zero-halogen standard wall cable for EMU according to claim 1, characterized in that: During the preparation and installation of the reinforcing core in step S5, during the twisting process of the aramid fiber bundles, a fiber positioning spacer is added every 5-10 mm to ensure the uniformity and stability of the twisted structure.
Citation Information
Cited By
Low-temperature-resistant torsion wind energy shielding flexible cable and manufacturing method thereof
CN120636911A